1987
DOI: 10.1248/cpb.35.3699
|View full text |Cite
|
Sign up to set email alerts
|

Studies on positive inotropic agents. IV. Synthesis of 5-(3-amino-2-hydroxypropoxy)-3,4-dihydro-8-hydroxy-2(1H)-quinolinone derivatives.

Abstract: Many 5-(3-amino-2-hydroxypropoxy)-3,4-dihydro-8-hydroxy-2(1H)-quinolinone derivatives were synthesized and examined for positive inotropic activity on the canine heart. These compounds were prepared by the reaction of 8-alkoxy-5-(2,3-epoxypropoxy)-2(1H)-quinolinone derivatives and various amines. Among them, 3,4-dihydro-8-hydroxy-543-(1,1,3,3-tetramethylbutylamino)propoxy]-2(1H)-quinolirrone hydrochloride (IIIf) was found to have potent positive inotropic activity with a relatively minor increase in heart rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…It is also well-known that most of the initial β-blockers contained an isopropyl- or tert -butylamine. Substitution of the nitrogen present within catecholamines by aralkylamines was found to produce β-adrenergic agonists having additional α-adrenolytic properties. , Similarly, it was found that N -aralkyl substitution could also confer α-adrenolytic properties to β-antagonists. , However, to the best of our knowledge, the influence of a direct aromatic substitution on the terminal amine upon adrenergic activity has scarcely been reported excepted in a few articles which described some N -aryl β-blockers which were found to be very weakly potent. , In the present article we describe the synthesis of a series of 31 new N -aryl dicyclopropyl ketone oxime ether derivatives and discuss the results from their examination in in vitro and in vivo β-adrenergic receptor assays.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…It is also well-known that most of the initial β-blockers contained an isopropyl- or tert -butylamine. Substitution of the nitrogen present within catecholamines by aralkylamines was found to produce β-adrenergic agonists having additional α-adrenolytic properties. , Similarly, it was found that N -aralkyl substitution could also confer α-adrenolytic properties to β-antagonists. , However, to the best of our knowledge, the influence of a direct aromatic substitution on the terminal amine upon adrenergic activity has scarcely been reported excepted in a few articles which described some N -aryl β-blockers which were found to be very weakly potent. , In the present article we describe the synthesis of a series of 31 new N -aryl dicyclopropyl ketone oxime ether derivatives and discuss the results from their examination in in vitro and in vivo β-adrenergic receptor assays.…”
Section: Introductionmentioning
confidence: 73%
“…9,10 However, to the best of our knowledge, the influence of a direct aromatic substitution on the terminal amine upon adrenergic activity has scarcely been reported excepted in a few articles which described some N-aryl β-blockers which were found to be very weakly potent. 11,12 In the present article we describe the synthesis of a series of 31 new N-aryl dicyclopropyl ketone oxime ether derivatives and discuss the results from their examination in in vitro and in vivo β-adrenergic receptor assays.…”
Section: Introductionmentioning
confidence: 99%
“…Certain quinolin-2(1H)-one (carbostyril) derivatives have been proved to possess antiplatelet, anti-inflammatory, anti-ulcer, vasodilatory, and phosphodiesterase inhibitory activities. [1][2][3][4][5][6][7][8][9][10][11][12] The cardiovascular and neuroprotective activities of certain 3,4-dihydroquinolin-2(1H)-ones substituted with various side chains have also been reported. 2,7,10,11,13 Recently, we have synthesized and evaluated the cardiovascular activities of certain a-methyleneg-butyrolactones bearing heterocycles such as coumarins, flavones, xanthones, quinolines, and quinolin-2(1H)ones.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] The cardiovascular and neuroprotective activities of certain 3,4-dihydroquinolin-2(1H)-ones substituted with various side chains have also been reported. 2,7,10,11,13 Recently, we have synthesized and evaluated the cardiovascular activities of certain a-methyleneg-butyrolactones bearing heterocycles such as coumarins, flavones, xanthones, quinolines, and quinolin-2(1H)ones. [14][15][16][17][18] Among these heterocycles, quinolin-2(1H)-ones proved to be the most active against platelet aggregation.…”
Section: Introductionmentioning
confidence: 99%